Po klęsce pod Walmojzą Korespondencja Lwa Sapiehy z synem Janem Stanisławem z pierwszej połowy 1626 roku - Ziober, Aleksandra (Wieki Stare i Nowe, 2019)
In January 1626 the Great Lithuanian Marshal, Jan Stanisław Sapieha, who was left behind by his father Lew in Livonia, was defeated by the Swedish army in Walmojza. News of the defeat quickly reached Warsaw, where the sessions of parliament were held, and it caused a great outrage among the noblemen and magnates who gathered there. It is from this period that the correspondence of the Great Lithuanian Marshal Lew Sapieha to his son Jan Stanisław dates back. The correspondence contains a great deal of interesting information concerning not only the military activities in Livonia but also the relations between the correspondents and their feelings, attitudes, opinions and reactions toward the changes that occurred on the Lithuanian political and military scene. The letters that were analysed furnish the image of a frustrated father who transferred his problems and failures on his son — the latter was already embarrassed by the defeat. It is likely that due to this the son’s mental health suffered.